Penerapan Kecepatan Mengetik Sepuluh Jari Sistem Buta Melalui Program Typing Master Pada Mahasiswa Program Studi D3 Administrasi Bisnis Politeknik Negeri Samarinda - Siti Nurhasanah; Putri Oktaviani (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2021)
Well-known typing skill is the 10 finger system typing method. The 10-finger typing method adheres to two principles, namely the ten-finger method and the blind system. The ten-finger blind typing skill is a learning result in the form of a pattern of entering text or numbers using a tool by pressing the keys or keys on the keyboard or keyboard, where the ten fingers work according to their respective duties with their eyes not looking at the keyboard but look at the script to be typed. The research method was carried out using the cosineger system. The measurement scale of respondents' answers used a Likert scale that ranged from 1 to 5. The results of the analysis of students majoring in Business Administration, Business Administration study program in the fourth semester of the 2019/2020 academic year, Samarinda State Polytechnic in the Keyboard Skill 2 course, totaling 122 (one hundred and twenty two) students from 5 (five) classes. The results obtained indicate that the typing master program is one of the blind system ten finger typing programs that is effective for students and easy to use, besides that it can train the typing speed of fourth semester students of the D3 Business Administration study program. The typing master program can also motivate students to improve their speed and accuracy in typing the ten-finger blind system.